Processing of Leachate Water into Liquid Fertilizer (POC) for Increasing the Economy of Chrysanthemum Farmers - Nasirudin Nasirudin; Rukmini; Diananto Prihandoko; Masrur Alatas; Yeremias Yanuarius Sedik (Jurnal Penelitian Pendidikan IPA, 2023)
The waste problem is a national problem that has derivative impacts, including the accumulation of waste in landfills which also causes pollution of locations around landfills for leachate production. TPST Piyungan which is the largest waste management site in Yogyakarta has a leachate treatment system but it does not work optimally. One of the leachate treatment technology options is a wetland system that can not only stabilize leachate by reducing heavy metal levels but can also produce liquid organic fertilizer (POC). This study aims to determine the performance of the wetland system using water bamboo to process leachate into liquid organic fertilizer and to determine the impact of testing on flower plants. Besides that, respondent analysis and economic analysis were also carried out. The results showed that the performance of the wetland system produced leachate NPK levels that were still below the standard liquid organic fertilizer, but its application to flower plants showed significant results in helping flower growth. The economic analysis also shows positive parameters and shows that this system is feasible for business development and has promising market potential.